Peripartum Emergency Hysterectomy, Risk Factors and Pregnancy Outcome at Al-Elwiyah Maternity Teaching Hospital - Salman, Hiba Awni; Al- Haidari, Taghreed Khalil (Journal of Science in Medicine and Life, 2025)
Background: Emergency peripartum hysterectomy (EPH) is rather an uncommon surgical procedure performed as a life-saving measure in cases of intractable obstetric bleeding. Although modern obstetrics as part of the technological scientific revolution have shown massive advances both medically and surgically, hemorrhage remains universally to be the leading cause of maternal mortality. A Middle East Region report shows that the percentage of EPH ranges from 0.39 to 5.38 per 1,000 deliveries. Intractable obstetric hemorrhage is a life-threatening condition caused by uterine pathology, uterine atony, uterine rupture and abnormal placentation. Aim of the study: To determine the risk factors, maternal and neonatal outcomes of cases of EPH at Al-Elwiyah Maternity Teaching Hospital. Patients and methods: A prospective cross-sectional study that was conducted in the Department of Obstetrics and Gynecology at Al-Elwiyah Maternity Teaching Hospital during a period extending from the 1st of Jan., 2022 to the 31st of Dec., 2022. All pregnant women who required EPH during the study period were included, with interpretation of risk factors, presentations, maternal and neonatal outcomes were insured. Results: The prevalence of EPH in all hospital deliveries was 0.6%, and 1.51% of all C/S deliveries. Sixty-two cases were undergoing EPH during the study period. Placenta accreta spectrum (PAS) was the cause of EPH in (59.7%), while postpartum hemorrhage (PPH) is the cause in (20.9%). Parity was significantly high in cases of EPH due to PAS and PPH with P value of 0.015, maternal age was significantly high in cases of EPH due to rupture uterus and cervical tear with P value of 0.002. Cases of EPH due to PAS and rupture uterus had significantly higher association P value < 0.0001, with an intensive care unit admission and the need for more blood transfusion than other causes of EPH. While the neonatal outcome was not differed in accordance with the indication of a hysterectomy. Conclusion: The main causes of peripartum hysterectomy in our hospital were mainly due to PAS followed by PPH. The single independent predictor for requirement of maternal intensive care unit admission was the indication for EPH, while neonatal intensive care unit admission was related mainly to gestational age and maternal hypertension.